2014
DOI: 10.1002/14651858.cd006105.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment before and during IVF or ICSI in women with polycystic ovary syndrome

Abstract: Analysis 1.6. Comparison 1 Metformin versus placebo or no treatment, Outcome 6 Number of oocytes retrieved per woman...... Analysis 1.7. Comparison 1 Metformin versus placebo or no treatment, Outcome 7 Mean total dose of FSH (IU) per woman........ Analysis 1.8. Comparison 1 Metformin versus placebo or no treatment, Outcome 8 Mean days of gonadotrophin per woman...... Analysis 1.9. Comparison 1 Metformin versus placebo or no treatment, Outcome 9 Cycle cancellation rate (a er ovulation induction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 37 publications
3
79
1
3
Order By: Relevance
“…• The use of metformin increase clinical pregnancy rate and decrease ovarian hyperstimulation syndrome (OHSS) risk during assisted reproductive technologies (ART) cycles [10].…”
Section: New Evidence-based Steps In Treating Pcosmentioning
confidence: 99%
“…• The use of metformin increase clinical pregnancy rate and decrease ovarian hyperstimulation syndrome (OHSS) risk during assisted reproductive technologies (ART) cycles [10].…”
Section: New Evidence-based Steps In Treating Pcosmentioning
confidence: 99%
“…While studies have demonstrated a decreased rate of OHSS with metformin administration for PCOS patients undergoing IVF [22], a randomized placebo controlled study did not show decreased rates of severe OHSS for patients with polycystic ovarian morphology [20]. Still, other techniques used to control for OHSS in PCOS patients such as agonist trigger have been shown to be successful in decreasing OHSS risks PCO patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…7 Cochrane review reported that metformin increased clinical pregnancy rates and reduced OHSS risk with no effect on live birth rate. 8 Smith et al have supported use of adjuvant metformin as a strategy for OHSS prevention starting at least 2 months before controlled ovarian stimulation. 9 Turan et al demonstrated that although MI was similar to metformin in prevention of OHSS, but increase in the ovarian diameter was the smallest in the MI treated group.…”
Section: Discussionmentioning
confidence: 99%